PREPARATION OF FUTURE TEACHERS FOR ECOLOGICAL-LOCAL WORK IN PRIMARY SCHOOL - Vysochan, Lesia; Milevska, Svitlana (Mountain School of Ukrainian Carpaty, 2019)
The social environment plays a crucial role in shaping the personality of the pupils. And not only the macro environment (the conditions of existence that surround the person in society), but also the microenvironment - the conditions created directly in the educational institution. Pedagogically competent micro-environment in the formation of personality arouses interest and desire to influence its character, which activates the process of education. The natural and social environment and their influence on the formation of personality allow us to distinguish local history as a complex science, combining information science (in turn complex), historical, art, history of literature, science and more. Local history as a pedagogical problem has always aroused great interest among researchers, since there is no other such comprehensive means of education and upbringing of man, which would include nature and history, economy and politics, culture and life of people of their native land. The result of the teacher's professional preparation for environmental studies is local knowledge, skills and skills. In addition, the future teacher is aware of the mutual influence of his environmental studies on the results of future professional activity, his role in the life of his native land, the moral orientation of local lore. He learns to look at the outside world not through the eyes of the consumer, but with the eyes of the creator, the figure, the active participant of transformations, the perfection of the surrounding life. Multiple subject teacher preparation for future professional activities is a holistic process, united by a community of pedagogical goals, tasks, and functions aimed at achieving the end result.